China's "soft power" and its influence on editorial agendas in South Africa. Issue 1 (2nd January 2016) - Wasserman, Herman
Abstract : In recent years, China's increased economic activity in Africa has elicited much scholarly and journalistic attention. The debates about China's presence in Africa have assumed the now familiar contours of asking whether China is a friend or foe, imperialist or ally, in addition to the meaning of these developments for the old powers of the USA and Europe. While the media has often facilitated these debates, in recent years China's activity in the African media sphere has also come under scrutiny. For the past several years, China has increased noticeably its influence on the African media space. Several state-owned Chinese media houses have established offices on the continent, especially in Kenya and South Africa. These media include the news agency Xinhua, the newspaper China Daily, China Central Television, and China Radio International. In South Africa, flows and contraflows of private media capital have also included investments both in and by China. Drawing on an exploratory survey of South African journalists across various platforms, the following aspects are investigated: Coverage: Journalists' views on the China–South Africa relationship in general within the context of the wider BRICS grouping and their views on the media coverage of this relationship. Norms and practices : Journalists' views on the meaning of China's media push on the continent and its involvement in the South African media landscape might mean for current norms (e.g., press freedom) and journalistic practices. Media as vehicle for soft power : Journalists' views on the usefulness of the Chinese media as a source in their own work and the influence of such media on their conceptions of the China–Africa relationship The article concludes with some preliminary observations about the challenges that Chinese soft power faces in South Africa.